Model Usaha Pembibitan Durian Bersertifikat Untuk Mendukung Pengembangan Buah Lokal Berkelanjutan Di Sumatera Utara - Fitriyenti, Fitriyenti; Martial, Tri; Noer, Zulheri (Owner : Riset dan Jurnal Akuntansi, 2024)
Durian, a superior product in North Sumatra, has high economic value and market opportunities. In an effort to develop a durian agribusiness business, the support for the availability of certified quality seeds from superior varieties greatly determines its success. The research aims to develop a nursery business model that is both economical and profitable, catering to the demand for certified quality seedlings and promoting sustainable agricultural development. The study employs a quantitative descriptive method to explain the nursery business's economic feasibility and ensure the sustainability of the provision of certified quality durian seeds. The research was carried out between March and June 2024 in three districts/cities, specifically Binjai, Langkat, and Deli Serdang, where the UPTD (Regional Technical Implementation Unit) of the Horticulture Main Seed Center (BBI) of the Food Security Office of Food Crops and Horticulture of North Sumatra Province operates a farming farm for the propagation of superior durian seeds. The purposive method was used to select a sample of 50 durian seed breeders, with assistance from the UPTD BBI. The data analysis method uses Structure Equition Modeling (SEM) to build the model. The results of the study show that business performance has an effect on local fruit development, the nursery business model has an effect on business performance, and certification has an effect on business performance. Overall, the results of this study show that to ensure the development of local fruits, nursery businesses must develop a business strategy that meets quality and quantity standards so that they can ensure the sustainability of the supply chain from producers to consumers.